Solidago virgaurea L. Plant Extract Targeted Against Candida albicans to Reduce Oral Microbial Biomass: a Double Blind Randomized Trial on Healthy Adults - Isabelle Prêcheur; Yohan Rolland; Lilia Hasseine; François Orange; Adeline Morisot; Anne Landreau (MDPI AG, 2020)
Oral microbiome plays an important part on oral health and endogenous bacteria and fungi should not be eradicated. However, their proliferation must be controlled by oral hygiene care. In vitro, Solidago virgaurea ssp. virgaurea L. (SV) plant extract inhibits the adherence and hyphal formation of a fungus, Candida albicans. It reduces the biomass of Candida-bacterial biofilms but not fungal or bacterial growth. Unlike chemical antiseptics, like triclosan and chlorhexidine for instance, SV is a plant extract easily biodegradable. The purpose of this study was to assess the in vivo effectiveness of SV extract in reducing oral biomass. A randomized, double-blind clinical study, with dental plaque evaluation designed to assess the effectiveness of a fluorinated toothpaste containing SV (Bucovia™, Givaudan, Vernier, Switzerland) was conducted. Sixty-six subjects (SV group n = 33 vs. control n = 33) brushed their teeth twice a day for a 4-week period. Supragingival dental plaque was sampled. Total bacterial load (broad spectral bacterial quantitative Polymerase Chain Reaction (qPCR)), C. albicans and seven bacterial species were quantified by qPCR. In the Intervention group, there was a decrease of Total bacterial load (ΔD0D28 p = 0.005 and ΔD14D28 p = 0.026), Streptococcus mutans (ΔD0D14 p = 0.024) and C. albicans (ΔD0D28 p = 0.022). In the Control group Total bacterial load tended to decrease from baseline to day 28 (ΔD0D28 p = 0.062 and ΔD14D28 p = 0.009). Plaque Index and Gingival Index improved in both groups.